First record of the globally invasive crab, Charybdis hellerii (A. Milne-Edwards, 1867), in Benin, with notes on its taxonomy (Crustacea, Decapoda, Brachyura, Portunidae) - Dessouassi, Comlan Eugène; Lalèyè, Philippe A.; D’acoz, Cédric D’udekem (Zootaxa, 2019)
The Indo-Pacific portunid, Charybdis hellerii (A. Milne-Edwards, 1867), is a crab species native to the Indian and Western Pacific Oceans and has previously colonized the Eastern Mediterranean and the Western Atlantic. It is now recorded in the Eastern Atlantic, on the coast of Benin, where a thriving population has established. This invasive and widely distributed species exhibits morphological variations within and between populations, which are discussed in detail. Its current distribution is presented, and its future expansion along the West African coast and future impact on coastal ecosystems and local fisheries are the object of tentative forecasts. Illustrations of sexually mature specimens from different sizes and regions are presented, and their allometric, individual and geographical variations are discussed. A new synonymy and a new account on the taxonomy and the biology of the species are presented. Illustrations of the lectotype and the paralectotype of C. hellerii are also provided for the first time. Charybdis spinifera (Miers, 1884), C. merguiensis (De Man, 1887) and C. vannamei Ward, 1941 are here treated as subjective junior synonyms of C. hellerii. The holotype of C. spinifera and two syntypes of C. merguiensis are illustrated.